Enhancing transtibial limb socket design through topology optimization / Mohd Hazwan Mohamed Norli ... [et al.] - Mohamed Norli, Mohd Hazwan; Zaidy, Amer Fahmie; Mohd Anuar, Mohd Afzan; Mahmud, Jamaluddin; Ramlee, Muhammad Hanif; Abdullah, Abdul Halim (UiTM Press, 2025)
The prosthetic transtibial limb socket is the device that attaches the stump of the amputee to the prosthesis. Achieving a comfortable design and fit is crucial for satisfactory use over time. Many individuals using prosthetics with transtibial sockets encounter issues like discomfort due to heavy sockets and inadequate airflow, impacting their musculoskeletal health. This research aims to address these challenges by developing, evaluating, creating, and analyzing an innovative transtibial socket. To begin, precise measurements and the raw shape of the patient's stump are identified using 3D scan technology. This data is then utilized to construct a new transtibial socket, ensuring an exact fit for the stump's interior through 3D modeling. Autodesk Fusion 360 and Meshmixer are employed to edit and design the socket based on the 3D stump model. Topology optimization is utilized to evaluate various iterations of the socket design, aiming to achieve an optimal design with geometric constraints while ensuring breathability. Finite element analysis is conducted to determine the force distribution within the socket design accurately. Through the redesigning, optimizing, and analysis of the socket in this project, its performance is enhanced, thus resolving the issues experienced by patients.